β-tricalcium phosphate/calcium sulfate loaded with contezolid acefosamil (MRX-4) for antimicrobial potency, prevention and killing efficacy of MRSA biofilm - Jiang, Nan; Zhang, Xin; Liu, Zi-Xian; Wan, Hao-Yang; Huang, Mou-Zhang; Lin, Qing-Rong; Liu, Guan-Qiao; Chen, Peng; Yu, Bin (Frontiers in Pharmacology, 2025)
ObjectivesThis study aimed to evaluate the antimicrobial potency and duration of contezolid acefosamil (MRX-4) combined with gentamicin against methicillin-resistant Staphylococcus aureus (MRSA) biofilms in vitro. We also compared its performance, when delivered via calcium sulfate (CS) and β-tricalcium phosphate/calcium sulfate (β-TCP/CS) carriers, with the conventional vancomycin + gentamicin regimen.MethodsAntibiotic-loaded beads containing MRX-4 + gentamicin (C + G) or vancomycin + gentamicin (V + G) were prepared using CS and β-TCP/CS carriers. Antimicrobial potency and release duration were assessed using a modified Kirby-Bauer zone of inhibition (ZOI) assay. MRSA biofilm prevention and eradication were evaluated through colony forming unit (CFU) counting and confocal laser scanning microscopy (CLSM).ResultsC + G demonstrated prolonged antimicrobial activity, maintaining effective ZOIs for at least 40 days, whereas V + G lost activity by day 40 (P < 0.05). Both C + G and V + G significantly prevented biofilm formation and reduced CFUs by > 8 logs (P < 0.001), with no significant difference between carrier types. In biofilm eradication assays, both treatments reduced CFUs by 3–4 logs; however, C + G showed superior efficacy over V + G at day 3 (P < 0.01). CLSM confirmed substantial biofilm disruption and bacterial killing in C + G-treated groups.ConclusionMRX-4 combined with gentamicin, delivered via CS and β-TCP/CS carriers, exhibits superior and sustained local antimicrobial efficacy compared to vancomycin, particularly in eradicating MRSA biofilms.